2009
DOI: 10.1088/1751-8113/42/21/214042
|View full text |Cite
|
Sign up to set email alerts
|

Collisional recombination in strongly coupled plasmas

Abstract: The molecular dynamics model of collisional recombination in strongly coupled plasmas is developed in the frames of the fluctuation approach. A non-monotonic nonideality dependence of the collisional recombination rate is discovered for all multiplicities of ionization studied. The rate is drastically suppressed with respect to the extrapolation of the ideal plasma three-body recombination conventional expression. The mechanisms of the suppression are discussed. The value of the suppression agrees with the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…In contrast to the ionic plasma component, where such a pre-ordering leads to significant suppression of the heating due to the repulsive ionion interactions [92,93], the attractive electron-ion interaction is found to cause electron heating to Γ 0.5 irrespective of the initial state. This clearly excludes the existence of metastable, very strongly coupled twocomponent plasma states, in which recombination is suppressed by orders of magnitude, as has been suggested recently [63,64] on the basis of numerical simulations.…”
Section: Two-component Plasma Simulationssupporting
confidence: 77%
See 1 more Smart Citation
“…In contrast to the ionic plasma component, where such a pre-ordering leads to significant suppression of the heating due to the repulsive ionion interactions [92,93], the attractive electron-ion interaction is found to cause electron heating to Γ 0.5 irrespective of the initial state. This clearly excludes the existence of metastable, very strongly coupled twocomponent plasma states, in which recombination is suppressed by orders of magnitude, as has been suggested recently [63,64] on the basis of numerical simulations.…”
Section: Two-component Plasma Simulationssupporting
confidence: 77%
“…We further discuss simulations of two-component plasmas for various initial configurations and temperatures, that demonstrate strong disorder-induced electron heating to Γ ∼ 0.5. This conclusively excludes the possibility of a metastable plasma state with ordersof-magnitude suppression of recombination as suggested in [63,64]. Nevertheless, strong coupling effects on the recombination rate are found to have observable consequences during the short-time evolution of UCPs.…”
Section: Introductionsupporting
confidence: 76%
“…To study the recombination process in NP the approach [48] is used. It is found that dependence of collision recombination rate on nonideality is not a monotonous one.…”
Section: Nonideality Effects: Rate Of Recombinationmentioning
confidence: 99%
“…On the other hand, it is written in the text of the article about the disagreement at large times, as should be expected from the physical formulation of the problem. 2 Some theoretical arguments regarding suppression of the recombination in ultracold plasmas can be found, for example, in paper [12] and references therein. Anyway, even if the recombination is taken into account by the standard way [11], its influence on the general law of temperature evolution is quite small.…”
Section: Analytical Estimatesmentioning
confidence: 99%
“…(1) to avoid large integration errors during the close collisions, the Coulomb's potential was cut off of smoothed out at the small distances (e.g. 1/r was changed to 1/(r + r 0 ) or something like that) [12,16,17];…”
Section: Formulation Of the Modelmentioning
confidence: 99%